Social Life Cycle Assessment of Green and Burnt Manual Sugarcane Harvesting in the Northeastern Thailand - Thiwaporn Thuayjan; Jittima Prasara-A; Pornpimon Boonkum; Shabbir H. Gheewala (Environment and Natural Resources Journal, 2022)
Despite green sugarcane harvesting being promoted in Thailand, with some limitations on the use of harvesting machines, green sugarcane harvesting is practiced manually in many sugarcane fields. Although the environmental benefit seems clear, this harvesting practice’s social implications are yet unknown. This study assessed social performances of green and burnt manual sugarcane harvesting in North-Eastern Thailand, the region hosting the largest sugarcane plantation area, using the Social Life Cycle Assessment technique. Data collection was undertaken by surveys. The performance reference points method was applied to assess the different stakeholder’s social performances. Key stakeholder groups examined were workers, local community, and farm owners. The main social issues included in this study are fair wages, working conditions, health and safety, local employment, economic development, social responsibility, and satisfaction of occupation. The results showed that the social performances of green and burnt sugarcane harvesting were generally similar except for the local community group. This is mainly due to the health impact of sugarcane burning on the local community. Different issues cause the farmers to harvest the burnt sugarcane; for example, labor shortage in the harvesting season and the difficult working conditions for green harvesting, causing the farm owners to bear higher costs. For these reasons, mechanized harvesting is suggested to help promote green harvesting to reduce local air pollution. However, technology development is in urgent need to make the harvesting machines more affordable and applicable to all geographical conditions.